Investigation of Trypanosoma evansi in Sumatran Elephant (Elephas maximus sumatranus) in Indonesia Using Various Methods - Purnamasari, Kartika; Nurcahyo, Wisnu; Nursalim, Muhammad Tauhid; Suwanti, Lucia Tri; Estoepangestie, Agnes Theresia Soelih (Universitas Airlangga, 2024)
Trypanosoma evansi is a widespread hemoprotozoa that causes trypanosomiasis in both livestock and wildlife. One of the susceptible animals is the Sumatran elephant, which is included in the endangered species category. The infection of this parasite often develops into chronic and sub-clinical forms in elephants, therefore it may become unnoticed and hard to diagnose. This study aimed to analyze and evaluate the infection of T. evansi in semi-captive Sumatran elephants in Way Kambas National Park, Indonesia, using various diagnostic tests. The prevalence of T. evansi in a total of 53 Sumatran elephants was estimated using a card agglutination test for trypanosomiasis (CATT) in 2016. A longitudinal study was later conducted in 2019 using Giemsa stained blood smear (GSBS) and polymerase chain reaction (PCR). The results showed that 26.4% of samples (14/53) were positively detected by both CATT in 2016 and PCR in 2019, while GSBS was unable to detect the parasites in all samples. Furthermore, four individuals were confirmed to have persistent infections. This study concluded that the ability of CATT and PCR were more convincing over GSBS for the diagnosis of sub-clinical trypanosomiasis in Sumatran elephants. However, it is recommended to use a combination of CATT as a screening tool and PCR as a confirmatory test for reliable results.